Did general surgeons surgical spectrum changed over time? A retrospective comparative study in a South Indian tertiary care centre between 2009 and 2018 - Gade, Veena; Meegada, Someswara Rao; Alavala, Chakrapani (International Surgery Journal, 2020)
Background: General surgery discipline has fragmented into several subspecialties over the past. This division has affected the surgical spectrum of general surgeons. Studies comparing the changes in the general surgeon's work spectrum were done in the ’90s but not in the recent past. Our study aims to compare the surgical spectrum of general surgeons between two time periods in our institute. Methods: We performed a retrospective study comparing the elective surgeries performed by general surgeons in the year 2009 and 2018 in an academic tertiary care centre. Results: There was a 28.9% rise in the total number of elective surgeries (1567 vs. 2020) in our study. There was a significant rise in the mean age of surgical patients (39.7 years vs. 41.9 years) but with no change in M: F ratio (1.7: 1). There was a significant rise in Hernia surgeries and Varicose veins surgeries (p<0.001) along with a rise in anal surgeries (p=0.018). There was a significant decrease in Breast surgeries (p=0.02) and Thyroid surgeries (p<0.001). There was a dramatic rise in the laparoscopic cholecystectomy rate (23.2% vs. 52%) and a fall in the laparoscopic appendectomy rate (26.3% vs. 8%). Open inguinal hernia surgeries were the most common surgeries performed in both the years. Conclusions: There was an increase in the surgical volume for general surgeons but the surgical spectrum has narrowed. We recommend conducting periodic surgical audits in institutions to monitor and maintain the standards of surgeries performed by general surgeons.